2009
DOI: 10.1007/s11255-009-9619-9
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis glossary 2009

Abstract: A number of attempts to create a commonly accepted terminology regarding definitions and terms used for clinical entities, methods, problems, and materials encountered by health professionals involved in peritoneal dialysis (PD) were undertaken in the past, the last one in 1990. Later on, some relevant sporadic attempts in a number of textbooks have been made, but they did not include the whole spectrum of PD. This glossary is an attempt to address the need for a universally accepted PD terminology including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In recent surveys [11,12], nephrologists indicated that in an optimal setting, 45-56% of all end-stage renal disease patients should utilize home dialytic therapies [13,14]. In the present study, we reaffirmed that in the era of CKD clinics, the majority of incident end-stage renal disease patients may be transitioned to home dialysis.…”
Section: Discussionsupporting
confidence: 74%
“…In recent surveys [11,12], nephrologists indicated that in an optimal setting, 45-56% of all end-stage renal disease patients should utilize home dialytic therapies [13,14]. In the present study, we reaffirmed that in the era of CKD clinics, the majority of incident end-stage renal disease patients may be transitioned to home dialysis.…”
Section: Discussionsupporting
confidence: 74%
“…The peritonitis rate was calculated by dividing the sum of the number of months each patient spent on dialysis by the total number of peritonitis episodes experienced by all patients and is reported as the interval in months between episodes. Relapses were not counted as 2 separate episodes, but as 1 episode (5).…”
mentioning
confidence: 99%
“…Moreover, the risks of shifting patients to hemodialysis, especially with a tunnelled line, after a fixed time on PD in the absence of definite indications, could equal or even surpass the risk of ever getting EPS and could also impact negatively on the patient's quality of life [25,26].…”
mentioning
confidence: 99%